2000
DOI: 10.1007/pl00012928
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Hypovirulent Binucleate Rhizoctonia sp. to Control Banded Leaf and Sheath Blight in Corn

Abstract: Water agar, artificially infested soil and leaf sheath inoculation methods were used to assess the suitable time of application, varietal host response and persistence of Rhv7, a hypovirulent, binucleate Rhizoctonia collected from soil in the Philippines, to effectively control virulent Rhizoctonia soluni AG1-IA isolate RS36 on corn. With the water agar method, prior inoculation (2 to 3 days) with the biocontrol agent is essential to achieve maximum control of the pathogen. Disease protection was increased fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…On the other hand, several authors have reported that hypovirulent binucleate Rhizoctonia (HBNR) effectively controlled Rhizoctonia diseases in several plants (Burpee and Goulty 1984;Cardoso and Echandi 1987a;Ichielevich-Auster et al 1985;Villajuan-Abgona et al 1996;Pascual et al 2000). HBNR is also reported to control diseases caused by other pathogens such as damping-off disease caused by Pythium ultimum (Harris et al 1993) and black-shank disease caused by Phytopththora parasitica var nicotianae (Cartwright and Spurr 1998).…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, several authors have reported that hypovirulent binucleate Rhizoctonia (HBNR) effectively controlled Rhizoctonia diseases in several plants (Burpee and Goulty 1984;Cardoso and Echandi 1987a;Ichielevich-Auster et al 1985;Villajuan-Abgona et al 1996;Pascual et al 2000). HBNR is also reported to control diseases caused by other pathogens such as damping-off disease caused by Pythium ultimum (Harris et al 1993) and black-shank disease caused by Phytopththora parasitica var nicotianae (Cartwright and Spurr 1998).…”
Section: Introductionmentioning
confidence: 93%
“…With the popularize and extensive planting of compact hybrids, the heavy use of nitrogen fertilizer, the increase in planting density and the application of plastic film mulching in maize production, the BLSB developed and spread rapidly, which caused a decrease of production of 10 to 20% or even higher (Huang et al, 2007;Tang and Tao, 1991;Yan et al, 2008). Some chemical control and preventive treatment to BLSB of maize has been advanced according to the occurrence pattern and prevalence condition of the disease, while these treatments have the shortage to use, high in cost or effect less in same condition (Yan et al, 2008;Chen et al, 2011;Ascual et al, 2000;Cheng et al, 2008;Huang et al, 2006). Therefore, breeding of cultivar with high resistance to BLSB were thought to be the most effective and economy method, but the lacks of resistance material hinder the breeding progress (Huang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A disease severity was rated from 0 to 4 described in methods after challenge inoculations with R. solani F-1 and S. rolfsii GUH-1 disease decline phenomenon was not observed with all the tested isolates, both pathogenic and hypovirulent isolates developed a high microbial biomass that positively contributed to the development of disease suppressive soils (Table 3). Isolates that have hypovirulent tendencies can possibly be used to induce suppressive soil in integrated pest management if judicially applied to the soil as reported by Villajuan et al (1996) and Pascual et al (2000). Their nonpathogenic nature, aggressive colonization ability and tolerance to a wide range of environmental conditions make these hypovirulent Rhizoctonia promising biocontrol agents (Muslim et al 2003).…”
Section: Discussionmentioning
confidence: 96%